MATERIALDEVELOPMENT: TEACHING ENGLISH FOR SMP STUDENTS IN BINTUNI BAY REGENCY WEST PAPUA - Sukristiningsih, Sukristiningsih (JURNAL TRITON PENDIDIKAN, 2017)
This writing is a library research that focuses on material development. Having a limitation of access to resources for teaching English as a foreign language in Bintuni Bay Regency and to attract students’ intension in learning English, so that the writer do the research entitled ‘Materials Development; Attractive Teaching English for SMP Students inBintuni Bay Regency, West Papua’. In EFL or ESL class, materials development is crucial. As students are learning a new language which is completely different from their first and daily language. Development teaching material is aims to attract and to help to easily understand the topics. Some of attractive materials offered by some scholars are varies and some of them are selected to be applied in teaching in SMP Bintuni. The selected materials are categories as flexible in using in all levels so that students in Bintuni easily to follow and also the affordable ones so that teachers can easily to prepare or to develop by themselves. Those materials are Realia, Games (Board race, Simon says, Word jumble race, and Hot seat), Audio / Tapes, and Pictures (Prediction for reading and listening activities, Teaching vocabulary, Word association pictures, Picture dictionary, Picture stories, Spot the difference, Choose the best picture, Memory test, Pictionary, and Personal picture map).